Don’t count your chickens before they hatch: Conceptualizing and exploring deviations from polls during public health app releases - Trang, Simon Thanh-Nam; Trenz, Manuel; Welf, Weiger (Journal of Information Technology)

A field experiment on ISP training designs for enhancing employee information security compliance - Nastjuk, Ilja; Rampold, Florian; Trang, Simon Thanh-Nam; Benitez, Jose (European Journal of Information Systems (VHB Jourqual 3 A))

Motivational Framing Strategies in Health Care Information Security Training: Randomized Controlled Trial - Keller, Thomas; Warwas, Julia; Klein, Julia; Henkenjohann, Richard; Trenz, Manuel; Trang, Simon Thanh-Nam (JMIR Medical Education)

Better (Cyber) Insured than Sorry? Unraveling Cognitive Factors in the (Non-)Adoption of Personal Cyber Insurance using fsQCA - Schütz, Florian; Ortiz de Guinea Lopez, Ana; Wolf, Tobias; Trang, Simon Thanh-Nam (Communications of the Association for Information Systems)

Keep Reward Or Return Fee – How Do Incentives In Product Return Management Influence Return Decisions And Future Customer Behavior? - Horsthemke, Johanna; Böhm, Eva (Proceedings of the 2025 AMS 25th World Marketing Congress)

Large‐Scale Interlaboratory Study Along the Entire Process Chain of Laser Powder Bed Fusion: Bridging Variability, Standards, and Optimization across Metals and Polymers - Kuşoğlu, Ihsan Murat; Garg, Sunidhi; Abel, Arvid; Balachandran, Prasanna V.; Barcikowski, Stephan; Becker, Louis; Bernsmann, Jan-Simeon; Boseila, Jonas; Broeckmann, Christoph; Coskun, Mert; Dreyer, Malte; East, Mark; et al. (Advanced Engineering Materials)
Laser powder bed fusion is a cornerstone technology for additive manufacturing (AM) of metals and polymers, yet challenges in achieving consistent reproducibility and process optimization persist. Addressing these requires a systematic understanding of the interactions between feedstock, process parameters, and final part characteristics throughout the entire production chain. This study presents results from a comprehensive interlaboratory investigation conducted by 32 research institutions, evaluating six feedstock, including nanoparticle‐modified aluminum alloy and polyamide powders, under standardized protocols. Data analysis encompasses 69 powder properties, 15 process parameters per print, and 78 part features, culminating in a dataset of over 1.2 million correlations. Advanced statistical methods and machine learning are employed to identify critical variability drivers, such as the impact of nanoparticle modifications on powder flowability and thermal conductivity, as well as the influence of process parameters on reproducibility. Newly introduced dimensionless figures of merit provide universal metrics to describe and predict thermal and mechanical interactions, simplifying process optimization and material characterization. The findings, supported by an open‐access dataset adhering to findable, accessible, interoperable, and reusable principles, advance understanding of material–process–structure–property relationships. They establish a benchmark for future research and lay the foundation for improving the reliability, quality, and sustainability of AM processes.

The importance of structure in transformation chaos: A Transformation Framework - Gräßler, Iris; Grewe, Benedikt; Fritzen, Marc (AHFE International)
Dynamic market conditions, technological disruption and social change require organizations to continuously adapt and evolve. However, studies on organizational change show that the majority of transformations undertaken fail because they are characterized by a lack of clarity, overload and ineffective measures. This paper shows how a clear structure as a critical success factor can make the chaos and challenges of a transformation manageable. The focus here is on a practice-oriented framework that divides a transformation into nine essential building blocks with activities that are critical to success. The structure of the framework is understood as a flexible organizing principle for a transformation without hindering creativity and dynamics. Case studies show the adaptability and applicability of the framework to different characteristics and dimensions of transformation. The transformation framework provides an operative structure and enables transformation managers for transparent orchestration and implementation of transformation.

Data-driven decision support in the design and controlling of systems engineering transformation: a maturity model - Graessler, Iris; Grewe, Benedikt; Felgen, Luc (Proceedings of the Design Society)
ABSTRACT: Challenges of increasing system complexity and the need for interdisciplinary collaboration are prompting companies to reorganize towards Systems Engineering (SE). As part of the implementation of large-scale transformation programs, transformation progress is of great interest to management and employees involved. Existing maturity models lack measurable variables and reliable forecast. For this reason, a maturity model for evaluating SE Transformation is developed, that builds on quantitative metrics and enables an overarching view on transformation considering cultural aspects. Literature-based criteria for evaluating SE Transformation lay the foundation for measures and referenced metrics and indicators. Due to its data-centricity, the model presented enables a more comprehensive, fact-based decision-making basis for the design and steering of SE Transformation programs.

SETup automotive: a Method for Systems Engineering Transformation in automotive industry - Graessler, Iris; Grewe, Benedikt (Design Science)
Abstract The increasing prevalence of embedded software in today’s vehicles is leading to growing complexity, which can only be managed effectively through the use of reliable interdisciplinary engineering processes. With this in mind, systems engineering (SE) is currently being introduced on a large scale into the automotive industry. Pilot projects have demonstrated the potential for implementing changes, but these have not yet been accompanied by viable implementation concepts for SE. In the context of the proposed application-based research, the SETup automotive method ( S ystems E ngineering T ransformation u nder p iloting in the automotive industry) is presented, which comprises a step-by-step procedure of introducing SE into large automotive companies. By introducing SE by pilot projects first, both an in-process tailoring of all processes, methods, tools and structures (PMTS) required for the introduction and an in-process validation of the pilot scheme elaborated by the pilot projects are achieved. The presented method builds upon fundamental approaches to change management, which have been developed over many years in both research and practice. It has been validated by the industrial practice of SE transformation at German car manufacturers and suppliers. As a result, decision-makers, transformation managers and systems engineers are provided with a scientifically based and field-tested set of steps for the introduction of SE in their own company.

Strategic Product Planning Model – Digital twins for circular products and production processes - Gräßler, Iris; Rarbach, Sven; Grewe, Benedikt (Industry 4.0 Science)

Model-based Impact Analysis for Engineering Sustainable Products in Value Creation Networks - Gräßler, Iris; Rarbach, Sven (Procedia CIRP)

Structuring Systems Engineering Transformation: A three-step cycle of Transformation - Gräßler, Iris; Grewe, Benedikt (Procedia CIRP)

Why I declare a conflict of interest and you should not - Acem, Ensar; Aczel, Balazs; Albayrak, Nihan; Brown, Nicholas J. L.; Dudda, Leonie A.; Elsherif, Mahmoud Medhat; Gjoneska, Biljana; Kowal, Marta; Krishna, Anand; Miłkoś, Szymon; Paruzel-Czachura, Mariola; Patel, Jay; et al. (Theory and Society)
Academic publishing is both an indication of scientific contribution and a currency for career advancement. This dual role gives rise to a normative scientific conflict: Does the structural incentive to publish constitute a conflict of interest (COI) that ought to be disclosed? In this paper, we address this conflict through an action research approach, engaging collaboratively and reflexively to answer four related questions: (1) What evidence suggests that researchers face a (financial) COI when publishing? (2) What are the benefits and drawbacks of explicitly acknowledging that publications function as academic currency? (3) How should such conflicts be disclosed? (4) Do mechanisms such as pre-registration and registered reports resolve these concerns? This paper contends that while researchers are clearly incentivised to publish, this interest need not necessarily constitute a conflict or be explicitly disclosed. Treating this issue as a normative scientific conflict does reveal the need for a shift in how researchers understand and navigate the subjective, self-interested dimensions of their work. We propose four key responses: (1) integrating discussions of COIs and biases more extensively into undergraduate science education, (2) promoting greater reflexivity in everyday research practice (e.g., through reflexivity journals, peer-led audit groups, and the reintegration of discussions on the historicity and cultural nature of research into scientific publications), (3) critically investigating institutional incentives and journal policies, and (4) proactively adopting methodological safeguards such as pre-registration. By addressing this conflict through action research, we demonstrate how normative tensions in science can be made productive — supporting both critical reflection and structural improvement.

Evolving Design for Assembly, Disassembly and Reassembly into a new paradigm: Design-for-Capabilities with Hybrid Decision Support as an enabler for circular products - Gräßler, Iris; Pottebaum, Jens; Nyhuis, Peter; Schmidt, Matthias; Grewe, Benedikt; Vollenkemper, Felix; Hesse, Thomas; Meinecke, Tim (Stuttgarter Symposium für Produktentwicklung (SSP) 2025)

Stages of Systems Engineering: An Analysis and Characterization of Systems Engineering Approaches - Gräßler, Iris; Grewe, Benedikt (Systems)
In the engineering of complex technical systems, Systems Engineering (SE) is a key approach that is becoming increasingly relevant in more and more industries due to the ever-increasing complexity of systems. Over the decades of practical application and research, various specializations and forms of the Systems Engineering approach have developed, but there has so far been a lack of an overarching context and positioning in meaningful stages for the introduction of Systems Engineering in companies. For this reason, this research will systematize common Systems Engineering approaches and bring them together in a stage model for Systems Engineering. Based on a systematic literature review, use cases are identified for each approach and stage, which support companies in selecting an approach suitable for their own organization.
Keywords: Systems Engineering Transformation; maturity; Systems Engineering stages; approaches; SE

Towards Frame-level Quality Predictions of Synthetic Speech - Kuhlmann, Michael; Seebauer, Fritz; Wagner, Petra; Häb-Umbach, Reinhold (Interspeech 2025)

Analyse und Modellierung eines induktiven Ortungsprozesses unter Berücksichtigung der elektromagnetischen Wechselwirkungen planarer Spulensysteme - Lange, Sven
Diese Dissertation befasst sich mit der Entwicklung eines induktiv-basierten Lokalisierungsverfahrens mittels planarer Spulen, das auf magnetischer Kopplung beruht. Grundlage ist die elektromagnetische Induktion, bei der sich die entstehende Spannung proportional zur Gegeninduktivität verhält. Das Verfahren arbeitet im physikalischen Nahfeld und im Frequenzbereich von einigen kHz bis MHz, um eine effiziente Kopplung ohne Ausbreitung elektromagnetischer Wellen zu gewährleisten. Im Vergleich zu etablierten Verfahren wie GPS oder Ultraschall zeigt die induktive Ortung Vorteile bei kurzer Reichweite, insbesondere durch hohe Genauigkeit im Zentimeterbereich und geringe Materialabhängigkeit. Zudem lässt sie sich in bestehende Technologien wie bei der drahtlosen Energieübertragung integrieren und durch Sensorfusion mit anderen Verfahren kombinieren. Zur Modellierung und Optimierung werden physikalische Eigenschaften von planaren Spulen und EM-Feldern analysiert und elektrische Ersatzschaltbilder eingesetzt. Die geometriebasierte Berechnung der Gegeninduktivität ermöglicht die Entwicklung und Bewertung geeigneter Ortungsalgorithmen. Stochastische Filterverfahren verbessern zusätzlich die Robustheit gegenüber Umgebungseinflüssen. Abschließend wird eine modulare Simulationsplattform vorgestellt, die als Grundlage für die Generierung von Trainingsdaten sowie zur Weiterentwicklung von Mess-, Ortungs- und Filtermethoden dient.

From simulation to metamodel to experiment: Evaluating the prediction accuracy of polynomial regression models for clinch joint properties - Einwag, Jonathan-Markus; Steinfelder, Christian; Wartzack, Sandro; Brosius, Alexander; Goetz, Stefan (Journal of Manufacturing Processes)

Surface functionalisation of additively manufactured AlSi10Mg by organophosphonic acid and PDMS grafting - Prüßner, Tim; Hoyer, Kay-Peter; Buitkamp, Nadine; Vieth, Pascal; Grundmeier, Guido (Materials Chemistry and Physics)

Das Linguistic Soundscaping im Elementarbereich. Ein methodischer Ansatz für die Erfahrung von sprachlicher und sprachbezogener Heterogenität. - Varga, Eva (Diskurse und Praktiken der Heterogenität. Pädagogisches Handeln in heterogenen Settings. Mit einem Fokus auf die Elementar- und Primarbildung.)